Responsabilidad social empresarial e imagen corporativa de la cooperativa de ahorro y crédito Nuestra Señora del Rosario - Huamachuco 2018 - Aguirre Contreras, Carmen Rosa (2020)
The main objective of this research is to determine the impact of corporate social responsibility on the corporate image of the savings and credit cooperative Nuestra Señora del Rosario - Huamachuco 2018. The research methods used are: Inductive-Deductive, Hypothetical-Deductive and Analysis – Synthesis. The design of this research is non-experimental, transsectal of descriptive type. Using the probabilistic method, simple random sampling, a sample of 151 partners was obtained and the main data collection instrument used is the questionnaire. Through the results of the research it is concluded that corporate social responsibility has a positive impact on the corporate image of the savings and credit cooperative Nuestra Señora del Rosario - Huamachuco 2018.